Pengaruh Uang Saku dan Penggunaan Media Sosial terhadap Perilaku Konsumtif Mahasiswa Universitas Negeri Surabaya: Studi Kasus: Program Studi S1 Ekonomi Islam Angkatan 2022 - Eliya Rahmawati; Dafina Nur Faiza; Miranda Dwi Febrianti; Cahya Dwi Rahmawati; Mohammad Abdul Rosyid; Nasyiwa Ega Palupi; Suci Wahyuni Haddad; Harun Al Rosyid (Jurnal Simki Economic, 2026)
In the digital era, student consumer behavior is influenced by pocket money and social media usage. Pocket money used for daily needs can come from parents or personal income through part-time work. Meanwhile, social media functions as a platform for accessing information, interacting with others, and receiving various advertisements. In this regard, this study aims to analyze the influence of pocket money and social media usage on student consumer behavior. Therefore, the data were analyzed using statistical tests such as validity, reliability, classical assumption tests, and multiple linear regression. This study shows that pocket money has no significant effect on student consumer behavior, while social media usage has a significant and positive influence. Simultaneously, pocket money and social media usage have a significant effect on consumer behavior, with a contribution of 55.1%. Of the two factors, social media has a more dominant role in driving student consumer behavior.